Traditional Chinese Medicine nursing of a patient with septic shock complicated with gastrointestinal dysfunction (1例脓毒症休克合并胃肠功能障碍患者的中医护理体会) - ZHANG Xiaotong (张小桐); CAI Weimin (蔡卫敏); LIU Shuhua (刘书华) (Association of Integrative Nursing, 2023)
This paper summarized the Traditional Chinese Medicine (TCM) nursing measures for a patient with septic shock complicated with gastrointestinal dysfunction. Based on the symptomatic treatment and TCM syndrome differentiation, a comprehensive nursing including TCM colon instillation, TCM external application, acupoint injection, auricular acupoint pressing, acupuncture were carried out to improve the patient's gastrointestinal function and quality of life. (本文总结1例脓毒症休克合并胃肠功能障碍患者的中医护理经验, 在对症治疗的基础上, 基于中医辨证, 实施中药结肠滴注、中药外敷、穴位注射、耳穴压丸、针灸等中医特色护理技术, 养护结合, 能有效改善患者胃肠功能, 提升患者生存质量。)